2011
DOI: 10.1111/j.1464-410x.2010.09687.x
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil administered once daily for lower urinary tract symptoms secondary to benign prostatic hyperplasia: a 1‐year, open‐label extension study

Abstract: Study Type – Therapy (cohort)
Level of Evidence 2b What’s known on the subject? and What does the study add? Phosphodiesterase type‐5 (PDE5) inhibitors (tadalafil, vardenafil, and sildenafil) are well‐known treatment options for men with erectile dysfunction and should be taken before anticipated sexual activity. Tadalafil is also approved for once daily use in men with erectile dysfunction. Recent 12‐week studies in men with benign prostatic hyperplasia (BPH) have shown once daily use of tadalafil significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 15 publications
5
87
0
8
Order By: Relevance
“…14,31 The results from these studies have consistently shown sustained efficacy of tadalafil 5 mg once-daily over a 1-year period with no unexpected safety findings.…”
Section: Tadalafil For Asian Men With Bph/lutsmentioning
confidence: 83%
“…14,31 The results from these studies have consistently shown sustained efficacy of tadalafil 5 mg once-daily over a 1-year period with no unexpected safety findings.…”
Section: Tadalafil For Asian Men With Bph/lutsmentioning
confidence: 83%
“…18 Research among men with or without erectile dysfunction (ED) and LUTS has shown that tadalafil has a beneficial effect on LUTS independent of the drug's benefit on ED. [19][20][21][22][23] Indeed, a head-to-head comparison of tadalafil with the alpha-blocker tamsulosin showed similar improvements of LUTS due to BPH with each agent.…”
Section: Pde-5 Inhibitionmentioning
confidence: 90%
“…[21][22][23][24] (A) The likely mechanisms of action stem from effects on smooth muscle relaxation, endothelial cell proliferation, improved blood flow, and activity on the prostatic efferent nerves. 25 (D) Currently, tadalafil (5 mg once daily) is approved in Brazil for the treatment of urinary symptoms associated with BPH.…”
Section: Phosphodiesterase-5 Inhibitors (Ipde5s)mentioning
confidence: 99%